Cultural Humility: A Proposed Model for a Continuing Professional Development Program - Jennifer L. Cox; Maree Donna Simpson (MDPI AG, 2020)
Continuing professional development (CPD) is an essential component of professional practice for registered health practitioners to maintain and enhance knowledge, skills and abilities. There are many topics that practitioners may pursue relevant to their practice environment, and, in recent years, providing culturally safe and respectful practice is an emerging area of need. Unfortunately, many health professionals, whilst willing to offer cultural safe healthcare, may be uncertain of how to enact that practice. The World Health Organisation recognises attainment of the highest possible standard of health as a basic human right, and cultural safety is increasingly becoming an expectation of health professionals. To address this need and the insufficiency of support in the literature, the authors have presented a discussion paper on various aspects of cultural safety and the underlying constructs, such as cultures, that support it. The discussion takes into account core constructs that signpost the path to cultural safety and recognises the role and accountability of all levels of the healthcare system, not merely the practitioner. Finally, we propose a model program for a cultural humility CPD activity incorporating pre-work, online modules, interactive workshop, reflection on professional practice and a post-workshop evaluation.